2019
DOI: 10.2903/j.efsa.2019.5692
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of APSA PHYTAFEED® 20,000 GR/L (6‐phytase) as a feed additive for chickens for fattening, chickens reared for laying and minor growing poultry species

Abstract: APSA PHYTAFEED ® 20,000 GR/L is a preparation of 6-phytase which is presented in solid and liquid forms. This additive is intended to be used as a zootechnical additive in chickens for fattening or reared for laying/breeding and minor poultry species for fattening or reared for laying/breeding. The 6phytase present in the additive is produced by a genetically modified strain of Komagataella phaffii. The production strain and its recombinant DNA were not detected in intermediate products used to produce the add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…In a previous opinion, the Panel described the additive and its manufacturing process including the production strain (EFSA FEEDAP Panel, 2019a).…”
Section: Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous opinion, the Panel described the additive and its manufacturing process including the production strain (EFSA FEEDAP Panel, 2019a).…”
Section: Assessmentmentioning
confidence: 99%
“…The safety aspects regarding the use of this additive in feed including the safety of the genetic modification of the production strain, the safety for the consumers, for the user and for the environment have been previously assessed (EFSA FEEDAP Panel, 2019a). The Panel concluded that the use of the product as a feed additive raises no concerns for consumer safety and for the environment.…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The FEEDAP Panel adopted an opinion on the safety and efficacy of APSA PHYTAFEED ® 20,000 GR/L (6‐phytase) as a feed additive for chickens for fattening or reared for laying and minor poultry species for fattening or reared for laying (EFSA FEEDAP Panel, ).…”
Section: Introductionmentioning
confidence: 99%